Relatedness between Medicine and the English Language Exploring the Symbiosis of Medicine and the English Language (Healing Words) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the intricate relationship between medicine and the English language, unraveling the profound impact language has on the practice and perception of healthcare. From the evolution of medical terminology to the nuances of doctor-patient communication, we navigate the linguistic landscape that shapes medical discourse. Through historical analysis and contemporary case studies, we illuminate how language serves as a vessel for medical knowledge, influencing diagnostics, treatment modalities, and patient outcomes. As we explore this symbiotic connection, the article aims to foster a deeper understanding of how language not only communicates the science of medicine but also molds the very essence of healing.